Validating heteronuclear 2D quantitative NMR. Issue 9 (15th February 2016) - Fardus-Reid, Fahmina; Warren, John; Le Gresley, Adam
Abstract : NMR is used extensively for accurate quantitation of simple analytes and can, with careful application, generate SI traceable measurements. Abstract : NMR is used extensively for accurate quantitation of simple analytes and can, with careful application, generate SI traceable measurements. Its application for more complex analytes is limited due to spectrum complexity and signal overlap. Due to its higher resolving power, 2D qNMR is starting to emerge as a viable quantitative technique for such complex analytes but brings with it a variety of sources of experimental bias not present in the simple 1D qNMR method. In order to claim SI traceability of 2D NMR techniques, these biases and additional sources of measurement uncertainty need to be quantified. This work evaluates the application of HSQC methods to perform quantitative analysis with minimal bias and using an internally standardised glucose assay as an example, to assess the variation between experimental and theoretical biases and discuss approaches to determine the measurement uncertainty with a minimum of method validation.